2011
DOI: 10.1007/s11250-011-9859-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shearing in a hot environment on some welfare indicators in Awassi lambs

Abstract: The aim of this study was to analyze the effects of shearing on the individual behaviors and rectal temperature profile during the day at hot environment in Awassi lambs. Twenty Awassi male lambs were randomly allocated into shorn (n = 10) and unshorn (n = 10) groups (28.8 ± 0.7 and 29.9 ± 0.7 kg, respectively) and were kept indoor during the experiment. The physiological and behavioral response variables measured were rectal temperature, standing, lying, feeding, ruminating, drinking, locomotor activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In the present study, the longer proportion of standing time and shorter lying time of the T0 group might be assigned to their effort to improve heat reduction by fascinating advantage of increased rational water loss, radiating surface expanse, and air crusade or convection by increasing its body surface area exposed to heat stress (Allen et al2015). In agreement with our findings, Dikmen et al (2011) also recorded lower lying and more standing behavior in shorn Awassi lambs to dissipate heat during the warmer part of the day. Animals occupy more time in standing without feeding and less time in lying as heat load increased (Legrand et al 2011;Kanjanapruthipong et al2015).…”
Section: Standing and Laying Behaviorsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the longer proportion of standing time and shorter lying time of the T0 group might be assigned to their effort to improve heat reduction by fascinating advantage of increased rational water loss, radiating surface expanse, and air crusade or convection by increasing its body surface area exposed to heat stress (Allen et al2015). In agreement with our findings, Dikmen et al (2011) also recorded lower lying and more standing behavior in shorn Awassi lambs to dissipate heat during the warmer part of the day. Animals occupy more time in standing without feeding and less time in lying as heat load increased (Legrand et al 2011;Kanjanapruthipong et al2015).…”
Section: Standing and Laying Behaviorsupporting
confidence: 93%
“…Animals occupy more time in standing without feeding and less time in lying as heat load increased (Legrand et al 2011;Kanjanapruthipong et al2015). The less lying and higher standing time in the current study is a mark of a lack of welfare in which the lambs tend to adjust their other behavior to compensate the bad effects of heat stress (Dikmen et al 2011;Silanikove 2000a).…”
Section: Standing and Laying Behaviormentioning
confidence: 79%
“…There are many different practices such as tagging, tail docking, dehorning, castration, weaning, vaccination, bathing, hoof trimming and shearing in sheep husbandry. Some of these practices are performed only once in the animal's lifespan, while others are neces sarily repeated periodically and these may cause an endocrine and metabolic response to occur in animals known as stress [1,2]. Animals that are exposed to stress react in species specific behavioral patterns that are also influenced by learned behavior, and there are differences between animals in response to these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…However, this traditional practice also means harvesting the fleece which provides protection against the external factors. In some of the studies performed in this field, it was reported that shearing increased the sen sitivity of the animals to thermal stress [8,1015], in others [2,16,17], that the removal of fleece did not have a signifi cant effect on the physiology of the sheep or that sheep were becoming more resistant to thermal stress after shearing. However, fleece properties of sheep have a very important role in the response of sheep to thermal stress [18].…”
Section: Introductionmentioning
confidence: 99%
“…Lying down is frequently related to resting; however, it also relates to other welfare states in sheep. For instance, increased lying time was related to heat stress in Awassi sheep (Dikmen et al, 2011). In lambs, a reduction in lying time is an indicator of pain after castration (Thornton and Waterman-Pearson, 2002).…”
Section: Discussionmentioning
confidence: 99%